DESCRIPTIVE-TEXT TEACHING MATERIALS BASED ON LOCAL WISDOM IN THE BORDER AREA FOR JUNIOR HIGH SCHOOL STUDENTS - Giri Indra Kharisma; Imania Kusuma Rahayu (Universitas Negeri Makassar, 2021)
The product of this research is in the form of a textbook which aims to facilitate students in learning to understand and to produce descriptive texts. All the reading passages presented in the textbook describe the local wisdoms in Belu, which is directly adjacent to Timor Leste. This research uses 4D development model consisting of 4 stages, namely: define, design, develop, and disseminate. Based on the validation results by experts and practitioners, the developed textbook had a percentage of higher than 85% with a very feasible category to be implemented. The results of the try-out of the product conducted on students showed a very good response because it obtained 92% feasibility with a very good category.